The characteristics of adverse reactions of three anti-prostate cancer drugs based on Vigiaccess database and bibliometric analysis - Wang, Jianqing; You, Jia; Huang, Weixing; Yuan, Chiting; Chen, Jiangjie; Wang, Feifei; Wang, Wei; Zhang, Liwei (Frontiers in Pharmacology, 2025)
BackgroundAndrogen antagonists, including apalutamide, darolutamide, and enzalutamide, play a crucial role in the treatment of prostate cancer. This research evaluated the adverse drug reactions (ADRs) associated with the use of these androgen antagonists as reported by the World Health Organization (WHO). Additionally, it compared the adverse drug reaction (ADR) profiles of the three drugs to identify which one presents the lowest risk for individualized patient use.MethodsThis study employed a retrospective descriptive analysis design. We collected adverse event reports for three marketed androgen antagonists from WHO-VigiAccess and analyzed them in combination with a bibliometric analysis. We calculated the percentage of adverse reactions reported for each drug to compare the similarities and differences in adverse reactions among the three drugs.ResultsA total of 172,020 adverse events (AEs) associated with three androgen antagonists were reported in VigiAccess at the time of this study. Our findings show apalutamide causes the most endocrine disorders. Darolutamide has the highest rate of blood and lymphatic disorders, while enzalutamide causes the most nervous system disorders. The ten most common ADRs identified were fatigue, rash, death, hot flush, diarrhoea, asthenia, nausea, dizziness, arthralgia, and decreased appetite.ConclusionThis study utilizes real data from WHO-VigiAccess, which offers valuable insights for clinical reference. On one hand, we confirm both existing and potential adverse effects associated with androgen antagonists. On the other hand, We analyzed the possible future research directions, thereby supporting the case for more scientific treatment.